Ronald Reagan - Tucker, Rosalyn (North Mankato, Minnesota Capstone Press, a Capstone imprint, 2014)
"Simple text and photographs present a biography of president Ronald Reagan"--
Famous people
Includes bibliographical references (page 23) and index
1 2 13
NEW_ZTN_GN
Keywords: Reagan, Ronald -- Juvenile literature; Motion picture actors and actresses -- Biography -- Juvenile literature; Presidents -- United States -- Biography -- Juvenile literature